Technostress Management Strategy in the use of Electronic Medical Records Among Healthcare Workers at RSIA Zainab Pekanbaru - Selsi Ayunda Nazli; Purwadhi Purwadhi; Nining Handayani (Journal Research of Social Science, Economics, and Management, 2026)
Digital transformation in the healthcare sector through the implementation of Electronic Medical Records (EMR) aims to improve service efficiency, yet it also generates technostress among healthcare workers. This study is based on the increasing psychological pressure and digital workload experienced by healthcare professionals at RSIA Zainab Pekanbaru. The objective of this study is to examine the planning, implementation, and evaluation of technostress management strategies in the use of EMR. The research method used in this study is qualitative case study design involving 10 informants, consisting of 4 doctors and 6 nurses, with thematic analysis supported by NVivo 15. The results indicate that the planning stage is still dominated by a technical, reactive, and top-down approach, leaving psychological needs of healthcare workers insufficiently addressed. In the implementation phase, the organization prioritizes operational efficiency over adaptive capacity and psychosocial support. Evaluation remains focused on system performance without considering user experience or cognitive workload. This study concludes that: 1.Planning should shift toward a human-centered approach by involving healthcare staff; 2. Implementation requires strengthening human aspects through capacity building and digital well-being policies; 3. Evaluation must be holistic, integrating digital well-being indicators and structured feedback mechanisms.